INTEGRASI PASAR BIJI KAKAO DI TINGKAT PETANI KABUPATEN PARIGI MOUTONG DAN EKSPORTIR DI KOTA PALU - Ihdiani Abubakar (Universitas Tadulako, 2019)
Cacao is one of the major crops cultivated in Parigi Moutong district. Most of the cacao farms are small-level holder. The cocoa beans from this district are marketed directly to exporters in Palu city via district traders and provincial merchants, then they send them to the destination countries. Even though the price of cocoa beans is high at the traders and exporters, the farmers have never benefited from such a high price. The fundamental problem the cacao farmers facing is their weakness position in the price determination. Non competitive market structure affects the behavior of marketing agencies in term of the pricing mechanism. Hence, this study was to investigate such a price relation as well as market behaviors. In the short term, there was no integration found between cocoa bean market at the farm level in Parigi Moutong district and at the exporter level in Palu city. It reveals that a change in the cocoa price at the exporter level does not affect the price at the farm level. However, in the long-term, the integration of those market levels will change the cocoa price at the farm level accordingly to the price changes at the exporter level. The study also clearly reveals that the farmers seem to have gained no significant benefit from the price changes in the exporter level. The prices are found to more volatile at the exporter level than that at the farm level. It support the hypotheses that the marketing system is inefficient to convey products from farmers to exporters as indicated by a high marketing margin, a low farmer’s share on the price they receive and low vertical market integration. Some efforts could improve the bargaining position of farmers including sustainable empowerment of farmer groups, government guarantee for agricultural facilities and infrastructures, improvement of infrastructures, control of appropriate price and information of the market price to farmers. Keywords : Bargaining, Cacao Farmer, Marketing System, and Price.